CONFLICT BETWEEN PASTORALISTS AND FARMERS IN NIGERIA AND ITS POTENTIALS FOR REGIONAL INSECURITY IN AFRICA - Angela Ajodo-Adebanjoko; Joy Ede Ukoje (International Studies Journal)
Pastoralists and farmers clashes in different parts of Nigeria have been on the increase since the return to democratic governance in 1999. While it is recognised that both parties have been living peaceably for decades, several factors have affected this relationship and have made the onset of conflicts inevitable. For instance, climate change, drought, desertification and flooding have necessitated the movement of herders from their base in the northern part of the country to the south for greener pastures, a move that has pitched them against southern farmers whose crops are often destroyed during such migrations. Furthermore, population explosion, blocking of traditional grazing routes, cattle rustling and banditry as well as manipulation of the crisis by the political elite, have all aided the exacerbation of the conflict. Sourcing data from theoretical and empirical evidence, this study examines the phenomenon of pastoralists and farmers conflict in Nigeria and their potential for instability in the African sub-region. Findings from the study show that tensions or any major confrontation between the Fulani and other ethnic groups in Nigeria could have a spillover effect on neighbouring African countries with repercussions on Africa’s security and stability. This is because the Fulani ethnic group is found across several African countries and transnational livestock migrations could draw in fighters from neighbouring countries. Besides, the conflict could articulate other types of conflicts on the continent. To manage the conflict, the author recommends that African governments should muster the political will to address the security challenges posed to the African continent by the conflict by reviewing the ECOWAS Transhumance Protocol among others.